Bioassay guided isolation of an antidermatophytic active constituents from the stembarks of Entada spiralis Ridl (Pengasingan komponen aktif antiderma secara berperingkat dari kulit pokok Entada spiralis Ridl.) - Harun, Aiza; Mat So'ad, Siti Zaiton; Mohd Hassan, Norazian (Universiti Kebangsaan Malaysia (UKM), 2015)
Entada spiralis Ridl. (Leguminoceae) is a liana or woody climber that grows in the wild in Malaysia and is locally known as ‘Beluru’ or ‘Sintok’. The isolation and characterization of the chemical constituent from an active fraction have been carried out since no previous study has determined any active components from the stem bark. Our previous study had revealed methanol extract of E. spiralis stem bark exhibited promising antifungal activity against three dermatophytes strains, namely Trichophyton mentagrophytes ATCC 9533, Trichophyton tonsurans ATCC 28942 and Microsporum gypseum ATCC 24102 that cause skin infection. This study was performed to elucidate the structure of active constituent known as ester saponin from the active fraction of E. spiralis stem bark. The fractions were prepared using fractionation process and repeated antifungal test was conducted to identify the most active fraction. The structure elucidation of this compound was based on spectroscopic data (1H,13C NMR, HMQC, HMBC and DEPT135) and comparison with literature. On the basis of spectroscopic analysis, the compound was identified as 28-α,L-rhamnopyranosyl-18,21,22-trihydroxy-12-en-29-(2-acetylamino-β-D-glucopyranosyl) triterpene ester. The current study provides important baseline information for the use of E.spiralis stem bark for the treatment of skin infection caused by the microorganisms investigated in this study.